Accelerating The Readiness of The H2 Plant Unit and Maintaining the Quantity of HCU Valuable Product During Repairs to The Radiant Tube Reformer Leak Using a New Radiant Tube Reformer Plugging Method at PT Pertamina Patra Niaga Refinery Unit II Dumai - Indra Harapan Situmorang; Akbar Putra Jhonem; Rudi Hermawan; Edward Cantona Taufan; Zulfajri Zulfajri (Asian Journal of Social and Humanities, 2026)
This paper presents an operational reliability case study from the hydrogen plant that supports the hydrocracking complex at PT Kilang Pertamina Internasional Unit II Dumai. A crack was identified in radiant tube Row A No. 10 in reformer 702-H-1, creating an urgent risk of hydrogen release, tube rupture, fire escalation, and prolonged production loss. The conventional corrective action, namely full retubing with a new tube and ceramic-on-ceramic (COC) restoration, required approximately 138 hours and depended on spare tube availability. To reduce downtime and avoid a multiplier effect on the hydrocracker value chain, the team developed a new plugging method that isolated the failed radiant tube by installing welded plugs at both the outlet and inlet sides instead of replacing the entire tube. An engineering design package was prepared using 3D modeling, stress analysis, material selection for SS 310 and HK40 components, and load verification at the design pressure of 20.5 kg/cm². The implemented method restored operation faster than the historical retubing route, achieving a repair duration of approximately 40 hours versus 138 hours for the previous method. Operational impacts reported by the plant included normal H? plant operation above 30k Nm³/h, preserved jet fuel quality, medium-risk work exposure instead of high-risk exposure, avoided costs of approximately IDR 244.8 million, and protection of HCU profit equivalent to around IDR 10 billion. The case demonstrates that a fit-for-purpose plugging strategy can be an effective emergency repair option for radiant tube failures when supported by engineering verification, fabrication control, and formal standardization